ANÁLISE TOXICOLÓGICA DE NANOTUBOS DE CARBONO DE PAREDES MÚLTIPLAS EM CAMUNDONGOS PRENHES - Nava, Alexandre (2010)
Carbon nanotubes (CNT) appear as a new class of materials that have special properties and are the focus of many studies in the biological area. Toxicity studies are important to evaluate the biocompatibility and the possible risks of exposure to the CNT. In this context, we evaluated the reproductive toxicity of exposure to multi-walled carbon nanotubes (MWCNT) in pregnant mice. To this end, pregnant females were exposed orally 100 μl MWCNT/day, suspended in PBS / Tween 80® at a concentration of 5 mg/ml and 15 mg/ml during the implantation period (1st to 6th day of pregnancy), organogenesis (7th to 12th day of pregnancy) or during the fetal period (13th to the 18th day of pregnancy). The females were evaluated for changes in weight and consumption of food and water throughout the experiment. In the 18th day of pregnancy, females were undergoing cesarean section and recorded the number of live fetuses, resorptions and dead. The fetuses were weighed, measured and fixed in 70% alcohol (v/v) for analysis of skeletal changes. Maternal organs, liver, kidney, spleen, heart and lung were collected, weighed and fixed in formaldehyde 10% (v/v) for histological analysis. There were mild signs of maternal toxicity, viewed mainly by histological organs and all embryofetal observed changes occurred in animals exposed during the period of organogenesis. Exposure to MWCNT at a dose of 0.5 mg/day showed an increase in the number of resorptions and reduced number of live fetuses in the control group. The exposure to MWCNT 1.5 mg/day showed an increase in the proportion of resorptions, the average of dead fetuses and a reduction in the proportion of live fetuses, resulting in increased rates of prenatal losses. Changes in body weight of fetuses measures were observed in a dosedependent. Analysis of the skeleton showed a marked delay of ossification, also in a dosedependent. These data support the conclusion that exposure to MWCNT at doses of 0.5 mg/day and 1.5 mg/day, cause an increase in losses and prenatal growth retardation, intrauterine, when administered during organogenesis, and these changes may be related to the direct action of the body MWCNT or fetal abnormalities observed in the morphology of the mother's organs.